An Investigation into New Zealand's Climate During the Last Glacial Maximum: a Climate Modelling Approach - Drost, Frank (11658412) (2006)
New Zealand's climate during the Last Glacial Maximum has been investigated using the UKMO global and regional models HadAM3H (GCM) and HadRM3H (RCM). SSTs and sea-ice were supplied from a set of prior coupled model (HadCM3) runs and all models were set up according to the glacial conditions as specified by PMIP. In the analysis of the global simulation, emphasis was placed on the climate of the Southern Hemisphere. Compared to the present day, the modelled climate of the LGM is mainly characterized by the different wind regimes, both in the zonal and meridional directions. In the zonal mean, the polar trough shifted equatorward, and the westerly wind increased slightly between approximately 30 degrees S-50 degrees S, and decreased poleward of this zonal band. At the same time, there was an increase in the number of and/or strength of southerlies between 35 degrees S-60 degrees S. This resulted in a reduction of the poleward zonal mean meridional heat transport, and an enhancement of the wave number 3 pattern in the mean zonal circulation. All these changes contributed to a weaker SAO during the LGM. Interannual variability was as today, dominated by the High Latitude Mode (HLM, or Antarctic Oscillation/Southern Annular Mode) and ENSO. For the LGM, New Zealand was about 2.5 degrees C-4 degrees C cooler than in a pre-industrial control simulation. The seasonal cooling was largest during winter. Excluding the Alpine region, the largest cooling geographically took place in the east of the South Island. Precipitation was in general reduced everywhere during the whole year, except for the east of the South Island. The westerly wind increased considerably over the North Island and the northern part of the South Island, but was weaker over the rest of the South Island. JJA was the exception with weaker westerly winds over all New Zealand which was probably related to enhance blocking during that season. The stronger westerly wind accentuated the cooling over the North Island, except for the eastern region, where it mainly enhanced the dry conditions by preventing the moist easterly winds coming ashore. The weaker westerly wind in the south on the other hand encouraged enhanced penetration of moist winds. The most dramatic change in the modelled New Zealand climate was the large increase in the number of southerlies in each region, which were capable of bringing very cold polar air over most of the country. It was probably mainly the changes in the winds that lead to the harshness of New Zealand's climate during the LGM, increasing the seasonality in temperature and precipitation. It is suggested that they had therefore a controlling influence on the existence of some of the vegetation types in New Zealand.